Proximal to distal approach in the treatment of tandem occlusions causing an acute stroke. (21st February 2014) - Spiotta, Alejandro M; Lena, Jonathan; Vargas, Jan; Hawk, Harris; Turner, Raymond D; Chaudry, M Imran; Turk, Aquilla S
Abstract : Introduction: A tandem occlusion is a rare presentation of acute stroke that involves an occlusion of the internal carotid artery at the bifurcation with an intracranial middle cerebral artery occlusion. This study describes the experience at our institution in treating tandem occlusions with a proximal to distal approach in the acute stroke setting. Methods: A retrospective review of acute strokes caused by tandem occlusions requiring thrombectomy were performed. Results: 16 cases were identified with a mean National Institutes of Health Stroke Scale score at presentation of 13.1±3.9. The proximal occlusion was crossed initially with a microwire in all cases. All carotid occlusions were treated with stenting, and intracranial vessel thrombectomy was performed with a variety of devices. Procedure related complications occurred in two (12.5%) patients. Eight patients (50%) achieved a good outcome (modified Rankin Scale score of 0–2). Conclusions: A tandem occlusion of the carotid artery at the bifurcation with a concomitant intracranial occlusion is a relatively rare and complex presentation of acute stroke. We have found that addressing the proximal lesion first and covering it with a stent prior to performing distal thrombectomy appears to be a safe and effective option in the treatment algorithm.